Prediction of Binding Mode of Secondary Metabolites in Apium graveolens to Bcl-2 - Kee P. Shan; Nyi M. Saptarini; Jutti Levita (Pharmacology and Clinical Pharmacy Research)
Developing new cytotoxic agent which has minimal effect against normal cell is requiredto reduce the side effects obtained from the existing chemotherapy agents. Celery (Apiumgraveolens) showed several pharmacology activities, including anti-cancer. This study wasconducted to predict and visualize the binding mode of ten secondary metabolites in A. graveolens,i.e., apigenin, caffeic acid, kaempferol, limonene, shikimic acid, chlorogenic acid,ascorbic acid, quercetin, eugenol and ferulic acid against Bcl-2. Navitoclax was employed asreference. Molecular dokcing simulation was performed using AutoDoc Vina v.1.5.6. Theresults showed that the interaction enery (Ei) ranged from -4.20 to -6.01 kcal/mol, whereasinhibition constant (Ki) were 40.15 to 842.29 μM. Kaempferol showed the best affinity toBcl-2 (Ei=-6.01 kcal/mol; Ki=24,21 μM). Hydrogen bonds were bond between kampferoland Lys20, Ser102, and Arg103, amino acid residues in Bcl-2.In conclusion,Keywords: anti-cancer, Apium graveolens, Bcl-2, navitoclax